AFL-CIO President Joins with APHA to Demand Coverage for all Children (Tufts Archival Research Center, 2007)
Article in Bureau of National Affairs Journal 19 November 1996. Discusses joint effort between AFL-CIO President Sweeney and American Public Health Association to cover all children. Touches on APHA's new public health agenda for children. Includes tobacco regulation.